2018
DOI: 10.1253/circj.cj-17-0080
|View full text |Cite
|
Sign up to set email alerts
|

Csk Regulates Blood Pressure by Controlling the Synthetic Pathways of Aldosterone

Abstract: represent extreme cases, because most hypertensive cases are not explained by a mutation in a single gene. 3 Further, the finding of genes that cause monogenic syndromes highlights the significant functions of the kidney and adrenal gland in regulating blood pressure. 2,3 Specifically, 10% of all monogenic forms of hypertension are estimated to have primary aldosteronism, suggesting that the homeostatic maintenance of aldosterone levels and the effect of aldosterone on kidney function are pivotal in keeping bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“… 34 ). Lower DNAm at cg26843110 associated with shorter GA at birth, and decreased expression of CSK , which is involved in trophoblast differentiation 43 , as well as blood pressure and aldosterone regulation 44 . Finally, cg17823829 (annotated to KDM5B ) was hypermethylated with MSDP.…”
Section: Discussionmentioning
confidence: 99%
“… 34 ). Lower DNAm at cg26843110 associated with shorter GA at birth, and decreased expression of CSK , which is involved in trophoblast differentiation 43 , as well as blood pressure and aldosterone regulation 44 . Finally, cg17823829 (annotated to KDM5B ) was hypermethylated with MSDP.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed lower DNAm with MSDP at cg26843110, which is within the body of the EDC3 gene, and is nearby to SNPs associated with BW (rs3784789 31 ). Lower DNAm at cg26843110 associated with shorter GA at birth, and decreased expression of CSK , which is involved in trophoblast differentiation 40 as well as blood pressure and aldosterone regulation 41 . Finally, cg17823829 (annotated to KDM5B ) was hypermethylated with MSDP.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure is a complex network regulated by a series of physiological pathways. It is reported that the C-terminal Src kinase (Csk) works as a negative regulator of SFKs and a core modulator of blood pressure physiologically via inhibiting the adrenal gland to synthesize more aldosterone, regulating the contraction, growth and migration of VSMs, changing in the blood volume and sodium absorption, ultimately affects blood pressure levels [32,33]. And it has been confirmed that gene silencing and Haploinsufficiency of Csk could increase blood pressure via up-regulating the active form of Src [34].…”
Section: Sfks and Hypertensionmentioning
confidence: 99%